2014
DOI: 10.1016/j.ciresp.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad de un sistema de seguimiento óptico de instrumental en cirugía laparoscópica para evaluación de destrezas motoras

Abstract: RESUMENIntroducción: En este trabajo se estudia la utilidad de un sistema de evaluación de destrezas quirúrgicas basado en el análisis de los movimientos del instrumental laparoscópico. Método: El sistema consta de un simulador físico laparoscópico y un sistema de seguimiento y evaluación de habilidades técnicas quirúrgicas. En el estudio han participado 6 cirujanos con experiencia intermedia (entre 1 y 50 intervenciones laparoscópicas) y 5 cirujanos expertos (más de 50 intervenciones laparoscópicas), todos el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In total, 2 studies on the Myo armband were identified. The first concluded that the combination of the Myo armband and voice commands provided the most intuitive and accurate natural user interface [141]. The second compared the Myo armband and LMC with traditional image manipulation methods in surgery and concluded that the new input modalities had the potential to become more efficient [58].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 2 studies on the Myo armband were identified. The first concluded that the combination of the Myo armband and voice commands provided the most intuitive and accurate natural user interface [141]. The second compared the Myo armband and LMC with traditional image manipulation methods in surgery and concluded that the new input modalities had the potential to become more efficient [58].…”
Section: Discussionmentioning
confidence: 99%